The Effect of Credit Access on Food Security of Small Fishermen in East Java - Asfi Manzilati; Yenny Kornita Sari; Suprayogi; Anthon Efani (HABITAT, 2023)
The development of access to credit in various developing countries has increased. Some of these studies show a positive and significant impact on the productivity of rural communities. Although several previous studies have proven the importance of credit in increasing the productivity of rural communities. The purpose of this study was to examine the effect of access to credit on the food security of small fishermen in East Java. Yet, the data was analysis using an ordinary least square (OLS) and an ordered probit model. The results of this study show that fishermen's food security is included in the borderline category. In this sense, the majority of small-scale fishing communities are classified as having moderate food security but cannot be said to be safe. Therefore efforts are still needed to improve the food security of small-scale fishing communities in East Java. Other findings show that credit, education, ship size, Fisherman groups and the number of fishing gears have a significant influence on the food expenditure of small-scale fishing communities in East Java. Meanwhile credit, education, multigear adoption and trip length have a significant effect on fishermen's food security. Therefore, to support food security, it is necessary to increase access to credit, increase education levels, ship size, join fishermen groups, so that the number of catches and the length of fishing trips will increase which will have an impact on increasing income, in the end food security will be achieved.